HUBUNGAN ASUPAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS PEKAUMAN BANJARMASIN - Wulandari, Auliya Putri; Harun, Lukman; Okvitasari, Yenny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Type 2 Diabetes Mellitus (T2DM) is a chronic disease closely related to lifestyle, including dietary habits and physical activity. Uncontrolled blood glucose levels can lead to serious complications if not managed properly. This study aimed to analyze the relationship between dietary intake and physical activity with blood glucose levels among T2DM patients at Pekauman Health Center, Banjarmasin. This research employed a quantitative design with a cross-sectional approach. The study population consisted of all T2DM patients actively registered in the working area of Pekauman Health Center, Banjarmasin, within the last three months, totaling 539 individuals. A sample of 84 T2DM patients was selected using a purposive sampling technique. Research instruments included dietary intake and physical activity questionnaires, as well as blood glucose data obtained from medical records. Data were analyzed using the Spearman Rank test to determine the relationship between variables. The results showed that most respondents had a sufficient dietary intake (58.3%) and low physical activity (55.9%). Meanwhile, the majority of respondents’ blood glucose levels were in the diabetes category (61.9%). The Spearman test revealed a significant relationship between dietary intake and blood glucose levels (p = 0.000; r = 0.466), as well as between physical activity and blood glucose levels (p = 0.000; r = 0.578). It is concluded that imbalanced dietary intake and low physical activity contribute to high blood glucose levels in T2DM patients.Keywords: Type 2 Diabetes Mellitus, Dietary Habits, Physical Activity, Blood Glucose Levels.